Marginality, adaptation and farming in the New Zealand high country - Steven Kelly; Willie Smith (Revue de Géographie Alpine)
New Zealand’s mountain areas are sparsely populated, and the direct impact of disasters in these areas is largely on agricultural communities and communication networks. Subject to earthquakes (mainly in the Southern Alps) and volcanic eruptions (on the Central Plateau of North Island) New Zealand’s mountain areas are more generally subject to problems of erosion and land slips and in the south, irregular, extreme snow falls. The impact of exceptionally heavy snow falls over the past 150 years of European settlement is relatively well documented. While modern technology might be thought to have lessened such impacts, the recent snowstorm of 2006 in South Canterbury highlights how such hazardous events continue to impact on communities in mountain and upland areas. The increased dependence on modern communication technologies and changes in the operation and management of modern farm systems are shown to compound the social and economic impact of such events. This impact is significantly modified by the size and structure of the farms concerned.